21 Level Asymmetric Inverter without Inversion Circuit with Reduced Switch Count - VIKASH P; L Vijayaraja; S.Ganesh Kumar (PREPARE@u® | IEI Conferences, 2021)
This paper gives a new design for asymmetrical Multi-Level Inverter without H-bridge and with reduced number of switch components. The proposed model produces 21 levels with only 10 switches and 3 unequal voltages to obtain a maximum voltage output. The modes of operation of the proposed circuit are discussed in detail in this paper and there by framing the switching sequence for the proposed circuit. Simulation of the proposed inverter is done for loads like Resistive and Reactive. From the simulation results, inverter performance is analyzed in terms of THD.